Growth and gonadal development of gynogenetic diploid Scophthalmus maximus - Cal, R. (Rosa); Vidal, S. (Sergio); Martínez, P. (Paulino); Álvarez-Blázquez, B. (Blanca); Gómez-Ceruelo, M.C. (María Castora); Piferrer, F. (Francesc) (Journal of Fish Biology, 2014)
The survival, growth, gonadal development and sex ratios of gynogenetic diploid turbot Scophthalmus maximus between 9 and 36 months of age were investigated. Gynogenesis was induced by activation of freshly collected eggs with diluted (1 : 10 with Ringer) and UVirradiated (30000 erg mm 2) sperm, followed by a cold shock at 1 to 0 C for 25 min, starting at 6 5 min after fertilization. The exclusive maternal inheritance of the resulting gynogenetic diploids was confirmed in all individuals used in the experiment by microsatellite markers. Mean total length and mass throughout the experiment was higher in the controls than in the gynogenetics. The gonadal development in gynogenetic males proceeded normally, and in gynogenetic females it was delayed during the first sexual maturation but was normal during the second one. The sex ratio was 1 male (M) : 1 female (F) in the controls, as expected, but 1 M : 3 F in the gynogenetics. In a second, independent experiment, carried out with fish originating from different broodstock, however, the sex ratio was 1 M : 1 F in the controls and 0 M : 1 F (i.e. 100% females) in the gynogenetics. Together, these results suggested that the main sex-determining genetic component in turbot fits well to female homogamety, in accordance with data from other flatfishes. These results indicate that it will be possible to obtain near or all-female turbot stocks through induced gynogenesis or by crosses involving hormonally sex-reversed fish. 2